Quasi-molecular hydrogen storage capacity of graphene quantum dots: A dispersion corrected DFT study - Khadilkar, Pranav; Samudre, Nikhil S.; Krishnamurty, Sailaja (Journal of Energy Storage, 2024)
Efficient storage of hydrogen, green fuel with the highest energy density, remains a pressing challenge. Among the several materials investigated for their potential hydrogen storage, 2D materials, like graphene, have advantages such as mechanical strength and large surface area but fail to store hydrogen reversibly. In this context, the present computational experiment demonstrates the potential of Graphene Quantum Dots (GQDs) with 24, 40 and 42 carbon atoms for their hydrogen storage capacity in quasi-molecular mode. Factors such as edge terminations, heteroatom doping, and anchoring of metal atoms are evaluated as a function of their storage capacity. The study clearly demonstrates an enhanced storage capacity of quantum dots, particularly, when a single Ti adatom is anchored on a 24 carbon atom GQD with a storage weight % of 2.24 % w/w. The storage weight % is further noted to increase as a function of the number of Ti atoms anchored on the GQD with the highest hydrogen storage weight % of 6.1 % w/w. Importantly, the adsorption of hydrogen molecule on the Ti atom is through a quasi-molecular mode and is driven by Kubas interaction. This type of interactions makes GQDs as viable storage materials at room temperature. Secondly, the work demonstrates that GQDs offer higher storage capacities of hydrogen molecules as compared to their 2D counterparts viz., graphene sheets, making them attractive candidates to be explored experimentally.
Keywords: Density functional theory; graphene quantum dots; Hydrogen storage; Kubas interaction; Quasi -molecular adsorption; Ti adatom